Adopting a test model for citizens’ complaints to indicate the organization’s orientation towards social responsibility - an analytical study in the General Company for Central Markets - ثامر ياسر البكري, (Iraqi Journal for Administrative Sciences, 2024)
Today, social responsibility has become among the most prominent goals that organizations seek to achieve in general, related to society and managed by the state in particular, so calling for the achievement of social responsibility in the organization's work process has become part of the comprehensive strategy for its work, and promoting clear visions in its interaction with the environment and in all ways. Its variables. Based on this matter, society, represented by the organization's clients and those dealing with it, represents the most influential and clear element in indicating the reality of social responsibility in the work of this organization compared to others. Hence, listening to the opinion of citizens through the complaints they present represents a clear applied direction in the organization's approach to social responsibility in formulating its strategy. From this standpoint, the Central Markets Company's employees' awareness index, in thought and practice, for dealing with citizens' complaints was adopted as an indicator to determine its commitment to achieving social responsibility as a goal it seeks to accomplish in harmony and response to the mission and objectives for which it was designed and which it works in light of achieving.